Sodium ferric phosphate pyrophosphate composite positive electrode material and preparation method thereof

By accurately controlling the molar ratio of elements and introducing carbon cladding in the positive electrode material of sodium ion battery, combined with a two-step heat treatment method, the NaFePO4 companion phase was successfully removed, solving its negative impact on electrochemical performance, and achieving high purity, low-cost material preparation and excellent electrochemical performance.

CN119812262APending Publication Date: 2025-04-11WUHAN LIGONG QIANGNA NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411978446.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

There are electrochemically inert sodium phosphate sodium-phosphate NaFePO4 in the positive electrode materials of existing sodium ion batteries, which affects the circulation, magnification and polarization properties of the material, and it is difficult to effectively remove its associated phase.

Method used

By precisely controlling the molar ratio of sodium, iron and phosphorus to 4:(3-y):4, 0

Benefits of technology

The preparation of a high-purity and low-cost sodium ferric pyrophosphate positive electrode material is achieved. There is no NaFePO4 companion phase in the material, which significantly improves the electrochemical performance and improves the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812262A_ABST
    Figure CN119812262A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ferric phosphate pyrophosphate composite positive electrode material and a preparation method thereof. The composite positive electrode material comprises sodium ferric phosphate pyrophosphate and carbon, the surface of the sodium ferric phosphate pyrophosphate is coated with the carbon, the molar ratio of sodium to iron to phosphorus is 4: (3-y): 4 (0 < y < = 0.5), the carbon content is 1-10 wt%, the composite positive electrode material does not contain a NaFePO4 associated phase, and the chemical formula of the composite positive electrode material is Na4Fe2.5 (PO4) 2 (P2O7) C. The preparation method comprises the following steps: adding iron oxide, a sodium source, a phosphorus source and a carbon source into water to prepare a mixed solution, drying at 80-120 DEG C to obtain precursor powder, sintering in air at 150-200 DEG C for 5-20 minutes to form a semi-finished body, crushing, and finally sintering at 500-550 DEG C for 8-12 hours under the protection of argon or nitrogen to obtain a finished product. The adopted raw materials are cheap and easy to obtain, the temperature and time are accurately controlled through a unique two-step heat treatment method, generation of a NaFePO4 associated phase is effectively avoided, the electrochemical performance of the electrode material is remarkably improved, and the electrode material has important application value in the field of sodium ion secondary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and more specifically relates to a sodium iron phosphate pyrophosphate composite positive electrode material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries are considered to be the most promising alternative to lithium-ion batteries due to their abundant sodium resources, low cost and high safety performance. In recent years, great efforts have been made to develop key technologies such as cathode materials, anode materials and electrolytes for sodium-ion batteries. However, the development of cathode materials for sodium-ion batteries is restricted due to the inevitable disadvantages of large sodium ion radius and low standard electrochemical potential.

[0003] So far, the main cathode materials studied include transition metal oxides, Prussian blue compounds and polyanionic compounds. Among the polyanionic cathode materials, iron-based polyanionic cathode materials have good application prospects due to their strong structural stability, excellent cycle performance, low price and good safety. Among them, NaFePO synthesized by common solid or liquid phase methods is 4 They are all electrochemically inert sodium iron phosphate mineral structures. There is no sodium ion diffusion channel in this structure and it cannot be used as a positive electrode material for batteries. 4 Lithium removal and sodium insertion can synthesize NaFePO with olivine structure 4 However, due to its complex synthesis process, its future development and application are limited. 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 ) Due to its high theoretical specific capacity (128.9 mAhg-1), cheap and readily available raw materials, simple synthesis process, and good cycle performance, it has been confirmed to be an electrochemically active iron-based polyanion positive electrode material suitable for large-scale energy storage systems. However, sodium iron pyrophosphate is very likely to produce electrochemically inert sodium iron phosphate ore NaFePO during the synthesis process. 4 Its content directly affects the electrochemical properties of sodium iron pyrophosphate positive electrode materials such as cycle, rate, and polarization.

[0004] Patent document CN202410539875.2 discloses a sodium iron phosphate pyrophosphate positive electrode material, a preparation method and its application. The positive electrode material includes sodium iron phosphate pyrophosphate and carbon. Specifically, a precursor powder containing a sodium source, an iron source, a phosphorus source and a carbon source is sintered to obtain the sodium iron phosphate pyrophosphate positive electrode material. The sintering process performs sintering at both ends, a first sintering at a temperature of 250°C-350°C, a sintering time of 6h-24h, and then the temperature is raised to 400°C-600°C for a second sintering, and the second sintering time is 6h-24h. However, the prepared positive electrode material still contains NaFePO 4 , and the content is not low, which affects the performance of the final material.

[0005] Patent CN202411055545.2 A mesoporous sodium iron phosphate pyrophosphate material, preparation method and application thereof. The specific heat treatment process is also a two-step heat treatment. First, heat treatment is carried out, and the pre-sintering treatment temperature is 250-400°C, and the duration is 3-7h; then thermal shock is carried out, and the thermal shock temperature is 400-700°C, and the duration is 100-200s. The sodium iron phosphate pyrophosphate material is synthesized by a thermal shock method, and the surface of the material has a mesoporous structure of 10 to 50nm. It mainly uses a porous structure to effectively improve the ion migration efficiency, thereby improving the electrochemical performance of the sodium iron phosphate pyrophosphate material. However, the inert sodium iron phosphate ore type NaFePO 4 The problem of its production and content.

[0006] Therefore, it is necessary to develop high-purity, low-cost sodium iron phosphate pyrophosphate, and the electrochemically inert sodium iron phosphate pyrophosphate sodium iron phosphate type NaFePO 4 The extremely low or close to zero content has become one of the keys in the research of positive electrode materials for sodium ion batteries. Summary of the invention

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions: First, a sodium iron phosphate pyrophosphate composite positive electrode material is provided, comprising sodium iron phosphate pyrophosphate and carbon, wherein the carbon is coated on the surface of the sodium iron phosphate pyrophosphate, the molar ratio of the three elements of sodium, iron and phosphorus in the positive electrode material is 4:(3-y):4, 0<y≤0.5, the carbon content in the positive electrode material is 1wt%-10wt%, and the composite positive electrode material does not contain NaFePO 4 Associated phase. Further, the chemical formula of the sodium ferric phosphate pyrophosphate is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0008] The present invention also provides a method for preparing the above-mentioned sodium iron phosphate pyrophosphate composite positive electrode material, comprising the following steps: Step 1: Adding iron oxide, a sodium source, a phosphorus source and a carbon source into water to prepare a mixed solution; Step 2: Drying the mixed solution to obtain precursor powder; Step 3: Sintering the precursor powder in air to obtain a semi-finished product, and crushing the semi-finished product; Step 4: The crushed powder is sintered under the protection of an inert gas to obtain a sodium iron phosphate pyrophosphate composite positive electrode material.

[0009] Furthermore, it is characterized in that the molar ratio of the iron oxide to the carbon source in step 1 is (2-3):1; according to the molar ratio of Na:Fe:P in the mixed solution=4:(3-y):4, 0<y≤0.5.

[0010] Furthermore, the carbon source in step 1 is one or more of polyvinyl pyrrolidone, dopamine hydrochloride, ascorbic acid, tartaric acid, glucose, sucrose, starch, maltose, dextrin, and polyethylene glycol; the introduction of the carbon source can form a carbon coating layer on the surface of the sodium iron pyrophosphate material, increase the conductivity between the particles, and provide an electron transmission channel for the sodium iron pyrophosphate material to compensate for Na + The dynamic balance of charge during the sodium deintercalation process improves the electrochemical performance of the sodium iron pyrophosphate material. However, the introduction of excessive carbon sources will lead to a decrease in the relative content of active substances, thereby affecting the performance of the final product. Since chelating agents can also serve as part of the carbon source, the addition amounts of carbon source, chelating agent and iron oxide need to be coordinated with each other to obtain better electrochemical performance of the product.

[0011] The sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium acetate, sodium citrate, sodium dihydrogen citrate, disodium hydrogen citrate, sodium hydroxide, and sodium dihydrogen phosphate; The phosphorus source is one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and monosodium trihydrogen pyrophosphate.

[0012] Furthermore, the drying temperature in step 2 is 80-120°C.

[0013] Furthermore, the gas in step 3 is compressed air; the sintering temperature is 150-200° C., and the sintering time is 5 min-20 min.

[0014] Furthermore, the inert atmosphere in step 4 is one of argon and nitrogen; the sintering temperature is 500-550° C., and the sintering time is 8-10 hours.

[0015] The present invention also provides a positive electrode plate, comprising the above-mentioned sodium iron phosphate pyrophosphate composite positive electrode material or the sodium iron phosphate pyrophosphate composite positive electrode material prepared by the above-mentioned method.

[0016] Another aspect of the present invention provides a sodium ion secondary battery, comprising the above-mentioned positive electrode plate.

[0017] Compared with the prior art, the present invention has the following advantages: (1) The present invention precisely controls the molar ratio of sodium, iron and phosphorus to be 4:(3-y):4, 0<y≤0.5, and the carbon content to be 1wt%-10wt%. This precise composition control helps to optimize the electrochemical properties of the material, ensure efficient ion transmission and stable electrochemical reactions during the charge and discharge process, and improve the energy density and cycle life of the battery.

[0018] (2) The raw materials used in the preparation process include sodium sources such as iron oxide, sodium carbonate, sodium bicarbonate, phosphorus sources such as phosphoric acid, sodium dihydrogen phosphate, and carbon sources such as polyvinyl pyrrolidone and glucose. These raw materials are widely distributed in nature and have low cost, which greatly reduces the production cost of the materials, is conducive to large-scale industrial production, and improves the market competitiveness of the products.

[0019] (2) Sodium iron pyrophosphate was prepared by a two-step heat treatment method, and the temperature and time of the two heat treatments were controlled to reduce the NaFePO 4 The production of associated phases makes the composite material free of NaFePO 4 The presence of associated phases in the positive electrode materials of sodium ion batteries will seriously affect the electrochemical properties of the materials, such as cycle, rate, polarization, etc. However, the composite positive electrode material of the present invention does not contain the associated phase, so that the electrochemical properties of the material are significantly improved, providing a better quality positive electrode material foundation for the efficient operation of sodium ion batteries. Improve the electrochemical properties of electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0021] Figure 1 The XRD spectrum of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 of the present invention; Figure 2 The XRD spectrum of the sodium iron pyrophosphate positive electrode material prepared in Comparative Example 3 of the present invention; Figure 3This is the SEM spectrum of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 of the present invention; Figure 4 This is the TG spectrum of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 of the present invention; Figure 5 The charge and discharge curve of the sodium ion battery prepared in Example 1 of the present invention at a current density of 0.1C. DETAILED DESCRIPTION

[0022] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0023] It should be understood that when used in this specification and the appended claims, the term "comprising" indicates the presence of described features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or collections.

[0024] In order to simplify the drawings, only the parts related to the present invention are schematically shown in each figure, and they do not represent the actual structure of the product. In addition, in order to simplify the drawings and facilitate understanding, in some figures, only one of the parts with the same structure or function is schematically drawn or marked. In this article, "one" not only means "only one", but also means "more than one".

[0025] It should be further understood that the term “and / or” used in the specification and appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0026] In the embodiments shown in the drawings, the indications of directions (such as up, down, left, right, front and back) used to explain the structure and movement of the various components of the present invention are not absolute but relative. These descriptions are appropriate when these components are in the positions shown in the drawings. If the descriptions of the positions of these components change, the indications of these directions also change accordingly.

[0027] In addition, in the description of the present application, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0029] Example 1 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C, the preparation method of the positive electrode material is: (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0030] Example 2 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C, the preparation method of the positive electrode material is: 1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) adding 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 3.3 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 525°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0031] Example 3 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C, the preparation method of the positive electrode material is: (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) adding 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 3.3 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 500°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C. Example 4 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C, the preparation method of the positive electrode material is: (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 150° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0032] Example 5 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C, the preparation method of the positive electrode material is: (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 175° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0033] Example 6 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7)@C, the preparation method of the positive electrode material is: (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 5 min in a compressed air atmosphere to obtain a semi-finished product, and crushing the semi-finished product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0034] Example 7 A sodium iron phosphate pyrophosphate cathode material synthesized from iron oxide, the general formula of which is Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C, the preparation method of the positive electrode material is: (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 20 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0035] Comparative Example 1 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 400°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0036] Comparative Example 2 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) adding 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 3.3 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 600°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0037] Comparative Example 3 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) adding 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 3.3 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 300° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0038] Comparative Example 4 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) adding 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 3.3 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 100° C. for 10 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0039] Comparative Example 5 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 30 min in a compressed air atmosphere to obtain a semi-finished product, and crushing the semi-finished product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0040] Comparative Example 6 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) calcining the dry gel at 200° C. for 2 min in a compressed air atmosphere to obtain a semi-fabricated product, and crushing the semi-fabricated product; (5) The crushed semi-finished product was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0041] Comparative Example 7 (1) Using iron oxide, sodium dihydrogen phosphate and glucose as raw materials; wherein sodium dihydrogen phosphate is both a sodium source and a phosphorus source, iron oxide is an iron source, and glucose is a carbon source; (2) Add 9.6 g of sodium dihydrogen phosphate, 3.6 g of iron oxide, and 2.51 g of glucose to 100 mL of water to prepare a mixed solution; (3) drying the mixed solution at 80° C. to obtain a dry gel; (4) The crushed dry gel was placed in a nitrogen atmosphere and calcined at 550°C for 8 h to obtain Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C.

[0042] The Na prepared in Examples 1-7 and Comparative Examples 1-7 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C material according to Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7)@C: Conductive carbon black: binder is prepared with a mass ratio of 7:2:1 to prepare electrode slurry, and then coated on aluminum foil by blade coating. The aluminum foil is dried in an oven at 80°C for 8 hours. The dried electrode is pressed on a 12kg·cm 2 The tablets were pressed under pressure and then cut into 12 mm diameter discs using a slicer. The metal sodium sheet was used as the counter electrode, the glass fiber membrane was used as the diaphragm, and 1 mol·L -1 Sodium perchlorate (NaClO 4 ) ethylene carbonate (EC) and diethyl carbonate (DEC) solution was used as the electrolyte (the molar volume ratio of EC and DEC was 1:1), and CR2025 button cells were assembled in a glove box with a water oxygen value below 0.01ppm. The electrochemical performance of the assembled button cells was tested.

[0043] like Figure 1 The Na of Example 1 is shown. 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C material XRD pattern. Figure 1 It can be seen that the synthesis of sodium iron pyrophosphate Na using iron oxide 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C diffraction peaks of positive electrode materials and Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C standard cards completely overlapped with no impurity peaks, indicating that pure phase materials were successfully prepared.

[0044] like Figure 2 The Na of Comparative Example 3 is shown. 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C material XRD pattern. Figure 2 It can be seen that the synthesis of sodium iron pyrophosphate Na using iron oxide 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C diffraction peaks of positive electrode materials and Na 4 Fe 2.5(PO 4 ) 2 (P 2 O 7 )@C standard card has staggered peaks, indicating the presence of associated inert phase.

[0045] like Figure 3 The Na of Example 1 is shown. 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C material SEM picture. Figure 3 As can be seen, the use of iron oxide phosphate sodium iron pyrophosphate Na 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C cathode material has a spherical morphology and the product particle size is controllable.

[0046] like Figure 5 The Na of Example 1 is shown. 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C material charge and discharge curve at 0.1C current density, from Figure 5 It can be seen that the Na prepared in this embodiment 4 Fe 2.5 (PO 4 ) 2 (P 2 O 7 )@C as the positive electrode active material, the reversible capacity of the button half-cell at 0.1C reaches 115 mAh g -1 .

[0047] Table 1 Semi-finished product sintering temperature Semi-finished product sintering time High temperature sintering temperature First cycle discharge capacity (mAh / g) 50thCycle capacity retention rate (%) Example 1 200℃ 10min 550℃ 115.2 96.27 Example 2 200℃ 10min 525℃ 110.3 93.83 Example 3 200℃ 10min 500℃ 105.5 91.26 Example 4 150℃ 10min 550℃ 101.2 91.41 Example 5 175℃ 10min 550℃ 104.3 91.22 Example 6 200℃ 5min 550℃ 101.8 91.93 Example 7 200℃ 20min 550℃ 108.7 92.56 Comparative Example 1 200℃ 10min 400℃ 87.6 85.63 Comparative Example 2 200℃ 10min 600℃ 101.6 88.28 Comparative Example 3 300℃ 10min 550℃ 99.4 88.54 Comparative Example 4 100℃ 10min 550℃ 94.3 87.46 Comparative Example 5 200℃ 30min 550℃ 103.2 87.42 Comparative Example 6 200℃ 2min 550℃ 100.8 87.74 Comparative Example 7 none none 550℃ 88.6 86.23 By comparing the first discharge capacity and 50 cycle rates of Examples 1-7 and Comparative Examples 1-7, it can be seen that when the semi-body sintering temperature is controlled between 150°C and 200°C, the time is between 5min and 20min, and the high-temperature sintering temperature is between 500°C and 550°C, the synthesized sodium iron pyrophosphate does not produce an associated inert phase, and the assembled battery has excellent electrochemical performance. This is because during the sintering process of the semi-finished product, at a suitable temperature and time, the iron oxide and the carbon source chelating agent can be fully chelated, so that the iron element in the iron oxide exists in the form of ions and is dispersed in the phase of the semi-finished product sintered material. The final synthesized sodium iron pyrophosphate does not produce any associated inert phase. It can be seen from Comparative Examples 3-5 that too low or too high sintering temperature of the semi-finished product and too long sintering time of the semi-finished product are not conducive to eliminating the generation of associated inert phases, resulting in degradation of the performance of the electrode material. At the same time, it can be seen from Comparative Examples 1-2 that too high or too low high-temperature sintering temperature is also likely to produce associated inert phases during the preparation process, resulting in degradation of the performance of the electrode material. It can be seen from Comparative Example 7 that direct high-temperature sintering without sintering the semi-finished product is also likely to produce associated inert phases during the preparation process, resulting in degradation of the performance of the electrode material.

[0048] The above embodiments of the present invention are not only examples for explaining the present invention, but are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all the implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A sodium iron phosphate pyrophosphate composite positive electrode material, characterized in that: It includes sodium iron phosphate pyrophosphate and carbon, wherein the carbon is coated on the surface of the sodium iron phosphate pyrophosphate, the molar ratio of the three elements of sodium, iron and phosphorus in the positive electrode material is 4:(3-y):4, 0<y≤0.5, the carbon content in the positive electrode material is 1wt%-10wt%, and the composite positive electrode material does not contain NaFePO4 associated phase.

2. The sodium iron phosphate pyrophosphate composite positive electrode material according to claim 1, characterized in that The chemical formula of the sodium iron phosphate pyrophosphate is Na4Fe 2.5 (PO4)2(P2O7)@C.

3. A method for preparing the sodium iron phosphate pyrophosphate composite positive electrode material according to claim 1 or 2, characterized in that: The steps include: Step 1: Adding iron oxide, a sodium source, a phosphorus source and a carbon source into water to prepare a mixed solution; Step 2: Drying the mixed solution to obtain precursor powder; Step 3: Sintering the precursor powder in air to obtain a semi-finished product, and crushing the semi-finished product; Step 4: The crushed powder is sintered under the protection of an inert gas to obtain a sodium iron phosphate pyrophosphate composite positive electrode material.

4. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The molar ratio of the iron oxide to the carbon source in step 1 is (2-3):1; according to the molar ratio of Na:Fe:P in the mixed solution=4:(3-y):4, 0<y≤0.

5.

5. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The carbon source in step 1 is one or more of polyvinyl pyrrolidone, dopamine hydrochloride, ascorbic acid, tartaric acid, glucose, sucrose, starch, maltose, dextrin, and polyethylene glycol; the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium acetate, sodium citrate, sodium dihydrogen citrate, disodium hydrogen citrate, sodium hydroxide, and sodium dihydrogen phosphate; the phosphorus source is one or more of phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and monosodium trihydrogen pyrophosphate.

6. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The drying temperature in step 2 is 80-120°C.

7. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The gas in step 3 is compressed air; the sintering temperature is 150-200° C., and the sintering time is 5 min-20 min.

8. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: In step 4, the inert atmosphere is one of argon and nitrogen; the sintering temperature is 500-550° C., and the sintering time is 8-12 hours.

9. A positive electrode sheet, characterized in that: The invention comprises the sodium iron phosphate pyrophosphate composite positive electrode material according to claim 1 or 2 or the sodium iron phosphate pyrophosphate composite positive electrode material prepared by any one of the methods of claims 3-8.

10. A sodium ion secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method and application thereof

    CN118431439A

  • Sodium ferric phosphate pyrophosphate material with mesoporous structure as well as preparation method and application of sodium ferric phosphate pyrophosphate material

    CN119143098A

Cited By

  • Carbon-coated ion-doped ferric sodium pyrophosphate positive electrode material and preparation method thereof

    CN120440863A